Can non‐developers learn a simplified modeling notation quickly?. Issue 8 (7th June 2022) - Cervantes‐Ojeda, Jorge; Gómez‐Fuentes, María; Chacón‐Acosta, Guillermo
Abstract: The User Interface Transition Diagram (UITD) is a simplified modeling notation to describe the transitions between the UIs of a software system. It is designed to be used for customer‐developer s improving the models. This study investigates (i) which concepts of the UITD language are easy to understand and which ones require more effort to be understood and (ii) to what extent UITD comprehensibility depends on the user's programming skill level. A questionnaire was applied to a group of 334 non‐developers after they received a very brief explanation of the UITD concepts. The results were analyzed using statistical methods. The overall average score of the group was 70.42%, which is quite acceptable considering the briefness of the explanation. We observed a very low correlation between the subjects' programming skill level and their scores. This suggests that, even for people who have little or no programming skills, the entirety of the UITD symbols and concepts should quickly be understood with little further training. Abstract : This study investigates the understandability of the UITD graphic language. A group of 334 non‐developers was given a very brief explanation and then a questionnaire to test their understanding. The overall average score of the group was 70.42%, which is quite good. We also found a very low correlation between the subjects' programming skill level and their scores, which suggests that, with further training, the UITD should quickly be understood by any stakeholder during the requirements specification phase.